Differential Behavior of Non-albicans Candida Species in the Central Nervous System of Immunocompetent and Immunosuppressed Mice - Sanches, Marcelo D’Alessandre; Mimura, Luiza A. N.; Oliveira, Larissa R. C.; Ishikawa, Larissa L. W.; Garces, Hans G.; Bagagli, Eduardo; Sartori, Alexandrina; Kurokawa, Cilmery Suemi; Fraga-Silva, Thais F. C. (Frontiers in Microbiology, 2019)
The genus Candida includes commensal fungi that can cause local and systemic infections, frequently involving vital organs as the central nervous system (CNS). Candida spp. occupy the fourth place among infections that affect the CNS. Although the incidence of C. albicans is decreasing among patients under immunosuppressive therapies, the incidence of non-albicans Candida is increasing. In this context, the objective of this work was to evaluate the ability of non-albicans Candida species to spread to the CNS of immunocompetent and immunosuppressed mice. Adult female C57BL/6 mice were treated with prednisolone, intravenously infected with C. glabrata, C. krusei and C. parapsilosis yeasts and then evaluated at the 3rd and 14th days after infection. All Candida species disseminated to the brain from immunocompetent animals and induced local inflammation at the third day post-infection. The immunosuppression resulted in body weight loss, leukopenia and reduced IL-2 production by spleen cell cultures. Higher fungal loads were recovered from the CNS of immunosuppressed mice. Inflammatory infiltration associated to a Th1 subset profile was higher in brain samples of C. krusei immunosuppressed mice compared with immunocompetent ones. Additionally, C. krusei was able to transform into pseudohypha within microglia in vitro infected cells and also to induce elevated NO production. Altogether, these results indicate that C. glabrata, C. krusei and C. parapsilosis are able to disseminate to the CNS and promote local inflammation in both immunocompetent and immunosuppressed mice. C. krusei displayed a distinct behavior at the CNS triggering a local Th1 profile. The possible contribution of these non-albicans Candida species to other CNS pathologies as MS, Parkinson´s disease and Alzheimer deserves further attention.